Is early marriage practice a problem for women living in Istanbul? A qualitative study - BAYSAK, ERENSU; YORGUNER, NEŞE; AKVARDAR, YILDIZ (SPRINGER WIEN, 2021)
Early marriages (EM) adversely affect women's physical and mental health, education, and social status. The current study aimed to analyze effects of EM through the thoughts, experiences, and suggestions of women who were married under the age of eighteen in Istanbul, Turkey, and the key informants (e.g., social worker, psychologist, obstetrician) who have encountered EM. In-depth interviews were conducted with fifteen women who were married before age 18, recruited from psychiatry outpatient department and eleven key informants. Thematic analysis was used. Low educated, poor family environment with domestic violence and neglect of children, loss of parents, lack of access to education, and traditional social structure were stated as causes for EM. Families' attitudes about EM were characterized as their daughter's reputation would be tarnished which implied the daughter's premarital relationships would be perceived as immoral by community. All women experienced traditional, aggressive rituals for the first night of marriage, husbands were mostly insensitive, and coercive resulting a traumatic experience. Women were subjected to physical, sexual, psychological, and emotional violence; most of them were socially isolated after marriage with restrictions imposed by their spouses and spouses' family that limited communication with their loved ones. The women generally felt unprepared for adult sexual life and motherhood. In order to prevent EM, raising parents' awareness about EM, supporting girls' education, and enforcing legitimate regulations were recommended. Early marriages violate human rights, cause negative consequences for health both physically and mentally, and deepen social inequality for women. All the participants suggested a better functioning legislative arrangement. The male dominated society that legitimizes child marriages and other harmful traditional practices should be addressed.
Keywords: Early marriages; Women's mental health; Prevention; In-depth interviews; CHILD MARRIAGE; MENTAL-HEALTH; EDUCATION; AGE; TURKEY; GIRLS; INTERVENTIONS; ASSOCIATION